Conceptual Ideas of Narrative Pedagogy in Professional Formation of a Music Art Teacher - Oleksiuk, Olga; Rebrova, Olena (Journal of History Culture and Art Research, 2018)
Modern artistic education is considered in the context of the development of the spiritual potential of the individual on the basis of constructing a pedagogical process in line with the humanitarian practice. This practice involves the joint actions of "teacher-student" in the hermeneutic circle from life experience - to theoretical knowledge, reflection of practical activity - through the identification, formulation and solution of professional development tasks. In this regard, the pedagogical community is actively discussing the need to develop promising technologies that can provide a "breakthrough" in the development of education. The new technologies aim to solve a number of problems faced by a modern high school. Accordingly, the process of learning at higher art schools should be reoriented from acquiring knowledge and skills to forming abilities to gain this knowledge and skills independently. Therefore, for humanitarian knowledge in general and for artistic pedagogy in particular, a hermeneutical view is particularly productive. In an effort to overcome the traditional rational orientation and intellectualization of consciousness, it goes to the understanding of a man through the reflective re-evaluation of the spiritual experience of mankind, fixed not only in science, but also in art, in the culture as a whole, which, from our point of view, is very relevant. So there is a natural appeal to the narrative mode of knowledge, provided not by logics but imagination, because there are free images and fantasia in it. The linguistic design of the hermeneutic interpretation of a musical piece is associated with an appeal to meanings - individual meanings of words isolated from the objective system of relationships that are directly related to a specific musical piece. We referred suggestions regarding the phasing of the metaphor to narrative techniques. Mechanism of metaphor design is recommended to imagine as a series of mental operations: the emergence of the author’s intention, in search of the object (metaphor basis) that allows the author to express his idea. During this process due to the association some images and concepts arise and figurative, vivid ones should be chosen among them.